Influence of internal fill pattern, polishing time and Z-Axis orientation on the tensile strength of the 3D printed part - Seprianto, Dicky; ., Iskandar; R., Wilza; Adesta, Erry Yulian Triblas (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This fourth-generation industrial revolution is characterized by the existence of supercomputers, smart robots, drivers less vehicles, genetic editing and the development of neurotechnology, currently the manufacturing process is entering mass customization era that is how to make more high variety product with low price or known as build to order principle, customized product, but can be mass produced. One method that can answer the challenge is additive manufacturing using three-dimensional printing (3DP). In this research, making an object using 3DP use CAD data which then transformed into G-Code with FlashPrint© v.3.23.1 software. This study aims to determine the effect of the internal shape of the pattern fill, polishing time and z-axis orientation, to the tensile strength of test specimens made using Flashforge® Dreamer 3D Printer type Fused Deposition Modeling (FDM) with Polymaker PolySmooth™ material and refers to ASTM D-638 for the Type I. Factors investigated were Polishing Time, Internal Fill Pattern and Z axis Orientation with tensile strength response from test specimen. The test results data were analyzed using ANOVA with design type 2 factorial level and design 3 factorial interactions (3FI) modeled by Design-Expert® software. The result of the analysis revealed that the main factor that most influences to the tensile strength of the test specimens was the polishing time factor with the contribution percentage of 35%, while the interaction between internal fill pattern and z-axis orientation contributed 52%. © BEIESP.